Letter - Wigton Strike Committee, 7 May 1927 (page 1) (Wigton)
1926-05-07 "Letter - Wigton Strike Committee, 7 May 1927 (page 1)" [g0135001.jpg], 7 May 1926, Wigton Strike Committee Local Organisation